Design structure for CePr mixed oxide catalysts in soot combustion. Issue 33 (7th April 2017) - Fan, Lijia; Xi, Kang; Zhou, Ying; Zhu, Qiulian; Chen, Yinfei; Lu, Hanfeng
Abstract : A "molten state" appeared during heat treatment of CePr synthesized by a solid-phase grinding method with nitrates as precursors, which rapidly dispersed Ce and Pr. Therefore, CePr catalysts with different structures can be prepared, with catalytic activities independent of grinding time. Abstract : Four CePr mixed oxides with different structures were designed and synthesized using a solid-phase grinding method: a uniform solid solution of Ce and Pr (CePr-NN), Pr6 O11 -coated CeO2 (CePr-NO), CeO2 -coated Pr6 O11 (CePr-ON), and particle packing of CeO2 and Pr6 O11 (CePr-OO) were obtained, and characterized by XRD, H2 -TPR, TEM and TG. The results show that CePr-NN exhibits the best low temperature catalytic activity among the CePr catalysts. CeO2 is the major active phase on the surface of the CePr catalysts, and the use of Pr6 O11 as the framework maintains the thermal stability of the CePr composite oxide. Moreover, both the oxygen storage capacity and mobility of the active oxygen of the catalyst were improved with the incorporation of Pr into CeO2, resulting in a higher combustion rate. The "molten state" which appeared during the preparation when nitrate was used as the precursor, plays a significant role in the migration of Ce and Pr, and is the premise of forming different structures of solid solution or coating structure.